Perolehan Informasi Rating Buku Berdasarkan Gambar Sampul Buku Menggunakan Metode Scale-Invariant Feature Transform - Hamim Fathul Aziz; Yuita Arum Sari; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Along with the development of technology, almost kinds of all information are available on media online. The expanding technology are expected to make it easier to access all kinds of information in media online. As an example by searching book's rating automatically in media online by utilizing book cover. With the existence of a system that can find the book's rating by using the image on the cover getting from camera phone hopefully can make it easier and make it more fast to get rating information from the book, so it can make the customer do less mistaken when buying a book. Based on explanation above this research will uses scale-invariant feature transform to recognize the book's object in an image. Before find the appropriate image of the book; First, preprocessing will be doing on the image by searching for scale space; Then, find the key point or key point localization; Next, by calculation of pixel's angle or orientation assignment; Finally, transforming of the image descriptor or key point descriptor. On this research the image will be tested of this effect on light intensity, image rotation, and scaling. The result by matching test the image of book's cover using scale-invariant feature transform method has high accuracy in condition of bright light intensity and it has low accuracy when using image rotation and image scaling. The average accuracy can obtain in bright light conditions, rotation, and scaling are 90%, 57.5%, and 46.6% respectively.